Health status of minority Francophone seniors in Manitoba and access to services in french: Potential for social isolation - de Moissac, Danielle; Roch-Gagné, Margaux; Ba, Halimatou; Gueye, Ndèye Rokhaya; Ethier, Sophie (Human Development, Disability, and Social Change, 2016)
Francophone seniors in Manitoba represent a growing and vulnerable population, with poorer health outcomes and limited access to health and social services in the official minority language. To avoid isolation, support services are required, as chronic diseases and reduced mobility have a direct impact on both physical and social needs. The purpose of this study is to examine the current health status of seniors in the Francophone minority population of Manitoba and their access to health and social services in French. Demographic, social and health profiles were obtained for Francophone and non-Francophone Home Care clients in Winnipeg. Although diagnosed with similar health conditions as non-Francophones, Francophone seniors are less likely to be assessed with reduced cognitive performance and conditions making mood and behaviour unstable, such as dementia other than Alzheimer’s. Gaps in bilingual health services were identified for pharmacy, audiology and occupational therapy services, meal and transportation systems as well as support services for informal caregivers. Housing options with in-house support services provided in French are available and additionally provide opportunities for seniors to socialize with other Francophones. For the elderly living in singlehome units and their caregivers, support services provided in the official minority language are needed. Keywords: seniors, health, Francophone minority, home care

Sortir de la violence conjugale dans l’avancée en âge : les réalités des femmes vivant en milieu rural francophone minoritaire - Savard, Véronique; Marchand, Isabelle (Reflets, 2016)
L’article présente une revue critique de la documentation portant sur les réalités des femmes qui avancent en âge (50 ans et plus), vivent en milieu rural franco-ontarien et sont victimes de violence conjugale, ainsi que sur les enjeux qu’elles rencontrent dans leurs parcours de sortie de violence. Après avoir défini les catégories d’âge retenues, nous montrons notamment que ces femmes sont aux prises avec des contextes sociospatiaux, géographiques et économiques spécifiques, lesquels engendrent des barrières particulières dans la sortie de la violence. De plus, la situation de minorisation vécue sur le plan sociolinguistique accroît certains de ces obstacles, tels que l’accès aux services publics et sociaux. Nous concluons en mettant en relief la dimension critique de la recension effectuée et proposons des pistes de recherche. Mots-clés : violence conjugale, femmes âgées, femmes aînées, femmes qui avancent en âge, baby-boomer, milieu rural, francophone minoritaire